Local knowledge of Sundanese village people on traditional medicine: A case study in Cibeurih Hamlet, Nagarawangi Village, Sumedang District, Indonesia - Sintiami Ramadhani; Johan Iskandar; Ruhyat Partasasmita; Eneng Nunuz Rohmatullayaly (Society for Indonesian Biodiversity, 2021)
Traditionally, the Sundanese village people in West Java, to treat various common diseases, use traditional medicines made from various plants. The purpose of this study was to elucidate the knowledge of the Sundanese village people on various diseases, species of medicinal plants and parts of plants used to treat various diseases, sources of medicinal plant species, methods of processing and utilization of medicinal plant species, and source of knowledge on processing and utilization of medicinal plants. The method used in this research was mixed-methods, a mixture of qualitative and quantitative. Data collection techniques were carried out using semi-structured interviews with informants, structured interviews with respondents, and field observation. The results showed that there were 22 common diseases suffered by the people of Cibeurih Hamlet, Nagarawangi Village; 36 species of plants were recorded with the most dominant part of the leaf organ being used as medicine by the community; source of medicinal plants species mainly collected from the home garden; as well as the method of processing medicinal plants most often used by the community by boiling them, this knowledge is passed on from generation through parents.